The Hazel Wood - Albert, Melissa (Flatiron Books, 2018)
Seventeen-year-old Alice and her mother have spent most of Alice's life on the road, always a step ahead of the uncanny bad luck biting at their heels. But when Alice's grandmother, the reclusive author of a cult-classic book of pitch-dark fairy tales, dies alone on her estate, the Hazel Wood, Alice learns how bad her luck can really get.